Strategy to Improve Restaurant Taxpayer Discipline Through Issuing Warning Letters: Strategi Meningkatkan Kedisiplinan Wajib Pajak Restoran Melalui Pemberian Surat Teguran - Choirunnisa, Salsa; Imaningsih, Niniek; Fadil, Cholid (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The strategy of directly delivering warning letters to restaurant taxpayers has proven effective in improving taxpayer discipline in Surabaya. This is reflected in the 50.11% increase in Restaurant Tax (PBJT) realization. Direct interaction between tax officers and taxpayers also provides education on the importance of tax payments and their benefits for regional development. Challenges faced, such as taxpayer resistance and restaurant closures, can be addressed through a proper approach and flexible delivery schedules. This study concludes that delivering warning letters is a strategic step to encourage tax compliance, ultimately contributing to an increase in Regional Original Revenue (PAD). Future recommendations include enhancing tax awareness programs and developing technology-based methods for delivering warning letters to improve efficiency.